Stagnation in Identity-based Community: The Experience of Buton Youth Community - Wiroto, Dondick Wicaksono (Universitas Negeri Semarang, 2016)
Youth college student communites in Gorontalo are interesting to study because almost all of these communities are formed by the reason of ethnic and regional origin. This study uses a youth community, namely HIPPMIB (Himpunan Pemuda Pelajar Mahasiswa Indonesia Buton /Youth Association of Indonesian Students Buton) as the subject under study. At this time, HIPPMIB in Gorontalo is experiencing stagnation, as fewer members attending community events. There are several factors that cause the community to stagnate, such as the community does not function well and the alienation of the members from the community. Data collected through focus group discussions (FGD) illuminate that the youth community Buton in Gorontalo city needs to increase its understanding of the community, reflect its experience and reorganized the community so that cohesion remains intact and symptoms of alienation can be addressed.